The Capability of Water Spinach (Ipomoea aquatica) as Phytoremediator of Heavy Metal Chromium (Cr) - Dewi, Nova Aula; Rachmadiarti, Fida (LenteraBio : Berkala Ilmiah Biologi, 2025)
In the current era of globalization, humans are involved in various industrial and household activities with high intensity, which leads to water pollution in rivers. This water pollution is caused by the discharge of waste from industries and household waste containing chromium (Cr). To prevent the harmful effects of chromium, it can be addressed through phytoremediation methods. Consequently, the purpose of this investigation is to illustrate the potential of water spinach (Ipomoea aquatica) as a phytoremediation species capable of lowering chromium (Cr) concentrations in the cultivation medium. This trial was arranged under a randomized block design (RBD) involving a single treatment variable, namely the chromium (Cr) concentration within the medium at 0 ppm, 5 ppm, 10 ppm, and 15 ppm. Evaluation of chromium content, foliar chlorophyll levels, and fresh biomass was carried out through a one-way ANOVA followed by Duncan’s multiple range test. The treatment with 15 ppm chromium demonstrated a decrease of 11.853 ppm in the medium, yet it yielded the lowest chlorophyll value and the greatest reduction in biomass compared to the other treatments, reaching 10.167 mg/l and 142 grams, respectively, from an initial mass of 200 grams. A correlation coefficient of 0.796 was also identified, signifying a strong association between leaf chlorophyll concentration and the final fresh biomass of water spinach (Ipomoea aquatica). These outcomes confirm that Ipomoea aquatica possesses the capacity to uptake chromium (Cr).